A comparative analysis of the location behaviour of Japanese and European semiconductor manufacturers - Philip McCann; Tomokazu Arita (European Regional Science Association (ERSA), 2002)
Our paper analyses micro-level data from Japnese and European semiconductor manufacturers. We integrate a range of production technological indices with spatial data and regional economic variables in order to understand the principalissues determining the location behaviour of this sector. Our resuklts show that there are marked differences between the Japanese and European sectors of the industry, with many parts of this sector not corresponding either to an orthodox product life-cycle model or a simple Marshallian model of agglomeration beased on information-spillovers.
Keywords: 330